Financial Feasibility Study for The Use of KUPS Credit Scheme on Balinese Cattle Farming (A Case Study in a Farming Group “Satwa Winangun” of Tangkas Village in Klungkung Regency) - Putri, Budi Rahayu Tanama; Sukanata, I Wayan; Suciani, .; Sutama, I Nyoman Sutarpa (Advances in Tropical Biodiversity and Environmental Sciences; Vol 1 No 2 (2017): ATBESDO - 10.24843/ATBES.2017.v01.i02.p03, 2018)
This research aims to determine the financial feasibility on the farming business of breeding balinese cattle who uses KUPS Credit Scheme. Data was collected through observation and interview. Respondents were all members of the “Satwa Winangun” farmers in Tangkas village, Klungkung Regency. Financial feasibility is determined by evaluating the eligibility criteria such: NPV, Net B/C, IRR, and payback period. The assessment was based on 2 calculation systems, (1) calculation of cash costs in which forage and labor are not calculated as the cost (existing condition), and (2) total cost calculation, in which two components are calculated as cost. Based on the calculation of cash costs, cultivation of Bali cattle by utilizing KUPS credit in this village is financially feasible to be implemented. This was indicated by the NPV value of Rp. 274.103.000, IRR 20.16%, Net B/C 1.55, and investments has been able to return within 3.52 years. The result of sensitivity analysis shows that as far as KUPS interest rate is lower than 18.37% per year, this farming is still financially feasible. Breakeven point can be achieved when the number of cattle parents maintained is 37, or when the price of calves at the age of 6 months is an average of Rp. 1.764.022 per cattle. However, based on the calculation of total cost, this farming system is not financially feasible. This is shown by the negative NPV of Rp. -285.721.000, IRR 2.87%, and Net B/C 0,54. This farming system is not financially feasible despite the 0% / year KUPS rate. The break-even point can be reached when the price of calves at the age of 6 months averages Rp. 4.288.367 per cattle.